Impact Assessment of Fiscal Policy on Employment in Morocco: A Computable General Equilibrium Model Analysis - Bouijij, Soukayna; Maarouf, Abdelouahab (International Journal of Energy Economics and Policy, 2026)
Employment is a key driver of economic prosperity and a crucial tool in the fight against poverty. As such, governments must prioritize job creation in their policy agendas. This study focuses on the case of Morocco to assess the impact of expansionary fiscal policy on employment, using a Computable General Equilibrium (CGE) model, specifically the PEP-1-1 framework. Through simulations involving reductions in personal income tax and corporate tax, as well as increases in public investment in education and infrastructure, the findings indicate positive effects on job creation. However, these effects remain limited due to the slow pace of structural transformation in the Moroccan economy. Moreover, the comparative analysis reveals that fiscal policy measures have a more substantial impact on employment than public investment policies.